PENERAPAN MODEL PEMBELAJARAN STUDENT FACILITATOR AND EXPLAINING TERHADAP KEMAMPUAN PEMECAHAN MASALAH DALAM MATERI HIMPUNAN DITINJAU DARI GAYA BELAJAR SISWA KELAS VII SMP - Permanda, Saul; T, Ahmad Yani; Siregar, Nurfadilah; Meldi, Nadya Febriani; Gunawan, Fransiskus Hendra (Jurnal Penelitian dan Pembelajaran Matematika, 2024)
This research aims to determine the application of the Student Facilitator and Explanation learning model to students' problem solving abilities in set material, taking into account the learning styles of class VII SMP students. The method used is an experiment with a 2×3 factorial design, which involves two learning models, namely Student Facilitator and Creating and Problem Based Learning. The research results show that the Student Facilitator and Explanation model is more effective in improving problem solving abilities compared to the Problem Based Learning model. In addition, students with kinesthetic learning styles show better problem solving abilities than students with auditory and visual learning styles. This research emphasizes the importance of choosing a learning model that suits students' learning styles to improve problem solving abilities in mathematics.